ANALISIS METODE PELATIHAN KARYAWAN DALAM MENINGKATKAN PRODUKTIVITAS KERJA PADA PT.BANK RAKYAT INDONESIA CABANG BARRU - Naidah, HJ; Ilmi, Nur (Perpustakaan dan Penerbitan Unismuh Makassar, 2016)
This study aims to Analyze Employee Training Methods in Increasing Work Productivity At PT. Bank BRI Branch Branch. This research took place at PT. Bank Rakyat Indonesia CabangBarru. The population of this research is all employees of PT. Bank Rakyat Indonesia Barru Branch, amounting to 50 people with overall sampling or sample saturated. The analytical method used is simple regression analysis using SPSS v 17.Variable software in this research is Method of Training and Productivity work. The results of this study indicate that Training Methods have a positive / significant effect on employee work productivity. This can be interpreted that the better Productivity Work done then the training method will increase.This study aims to Analyze Employee Training Methods in Increasing Work Productivity At PT. Bank BRI Branch Branch. This research took place at PT. Bank Rakyat Indonesia CabangBarru. The population of this research is all employees of PT. Bank Rakyat Indonesia Barru Branch, amounting to 50 people with overall sampling or sample saturated.The analytical method used is simple regression analysis using SPSS v 17.Variable software in this research is Method of Training and Productivity work.The results of this study indicate that Training Methods have a positive / significant effect on employee work productivity. This can be interpreted that the better Productivity Work done then the training method will increase.